The mid-Republican Temples at Largo Argentina in Rome: Quarry Provenience and Construction History of Ancient Roman Lapis Albanus Tuff - Zink, Stephan; Diffendale, Daniel P.; Marra, Fabrizio; Pflug, Jens; Gaeta, Mario; Ceci, Monica (Römische Mitteilungen, 2024)
Recent research at Largo Argentina in Rome has resulted in the attribution of Italic-Ionic order architectural members in Lapis Albanus (‘peperino’) tuff to the earliest, 3rd century BCE phases of the so-called Temples A and C. Samples from both the architectural members and the ancient quarry sites of Lapis Albanus deposits at Marino (23 km from Rome) underwent ICP-MS trace-element and thin-section analyses. The results indicate that the material from Temple A is more geochemically homogenous, suggesting it was extracted from a restricted geographical area possibly corresponding to a single quarry, while Temple C reveals more heterogeneous sources. This study marks the first quarry proveniencing of contextualized Lapis Albanus building material, along with the first graphic reconstruction of the earliest columns of Temples A and C. Its results raise a number of questions regarding quarry extraction, distribution models, the constructional use of Lapis Albanus, and the stakeholders involved in the building processes.